Pengaruh Keputusan Investasi, Keputusan Pendanaan,Kebijakan Deviden, Hutang, Tingkat Suku Bunga, DanKepemilikan Manajerial Terhadap Nilai Perusahaan(Studi empiris Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia periode 2012-2014) - Sri Rahayu, Yayuk, Dr. Zulfikar, SE, M.Si (2016)
This research purpose to see the influence of factors that influence the company value that are investment decision, funding decision, devident policy, debt, interest rate, and the ownership of managerial. The population used in this research is annual report firms which is listed in Indonesia Stock Exchange at 2012-2014. Sample in this research is manufacturing company in Indonesia Stock Exchange at 2012-2014. This research use purposive sampling in carry out sample selection. There are 66 manufacturing company in Indonesia Stock Exchange at 2012-2014 is become sample in this research. Agency theory, the theory of capital structure, trade off theory and dividend irrelevant theory used to explain connection inter variable. Act of value of company in this research use content analysis based on the identification of setences act of value of company in the annual report. Test statistic used is multiple linear regression test. The result of this research find type of the funding decision, devidend policy, and debt did not influence the company value. While investment decision, interest rate, and the ownership of managerial significantly influenced the value company . However that totaly factors has influence toward act of the value company.